Place Experience of Nursing Home Courtyards: a Holistic Approach to Understanding Institutional Outdoor Environments - (:unkn) unknown (My University, 2015)
This dissertation research investigates place experience of three nursing home courtyards. Based on systemic place theories, each nursing home courtyard is conceptualized as place or a system consisting of three major subsystems: physical settings, people and rules of place uses. Place experience as the center of conceptualization is the result of interactions between them. Place experience is thus characterized by objective, subjective and consensual qualities of people-environment relationships. The research design follows the premises of pragmatic case study methodology; a mixed research method is employed that includes archival research of floor plans, photo documentation, a physical setting checklist and instrumented measures for physical environments; staff interviews, surveys and auditing evaluations for organizational and staff contexts; and resident interviews and behavior mapping for individual contexts and place rules. Through synthesizing different sources of data into experiential descriptions, this study suggests that each courtyard is a compound of nine desired experiential attributes including 1) privacy, 2) social interactions, 3) accessible space and built features, 4) safety & security, 5) sensory stimulation, 6) information awareness and spatial orientation, 7) familiarity, 8) sense of ownership and 9) participation in meaningful activities. Each courtyard is unique in its distinct composition of these attributes and arrangements of the three subsystems. Experience of social interactions is the shared experiential quality across the cases. The three courtyards are programmed as a social space but are not meant to be a place to mark ownership, show identities and create meaningful engagement. The shared nature is incongruent with residents’ experience of home gardens and gardening collected from the interviews. A relatively successful case is selected; it is a place with more equal emphases on the nine attributes. Its patterns of the three subsystems may guide a less effective case to make future improvement. Implications of the findings are considered at three levels. First, this study applied a pragmatic approach, which offers a means to generate a holistic understanding of institutional outdoor environments; this study may complement the current research dominated by a positivist approach. Second, the approach recognizes and acknowledges the multifaceted phenomenon of the courtyards; it describes sets of variables or quality indicators that may help further theoretical construction or the development of quality measure. Third, this comparative research highlights the importance of establishing a database of cases reports. The accumulation of successful cases would help identify effective patterns of the three subsystems. Shared features emerging from successful cases may represent findings with high generalizability.
Keywords: Gardem; Institutional Outdoor Environments; Landscape Design; Long-Term Care; Nursing Home; Place Experience